Transduction of hematopoietic stem and progenitor cells by an MECP2 lentiviral vector improves Rett syndrome phenotypes - Anderson, Joseph S.; Silverman, Jill L.; Lodigiani, Alyse L.; Barbaduomo, Camilla M.; Beegle, Julie R. (Frontiers in Drug Discovery, 2025)
IntroductionRett Syndrome is a genetic neurodevelopmental disorder caused by decreased levels of MeCP2. Due to mutations in the MECP2 gene, insufficient MeCP2 protein levels lead to clinical phenotypes including the loss of normal movement, decreased communication, seizures, sleep disorders, and breathing problems. Currently there is no cure for Rett Syndrome and the only means to help patients is palliative care directed to their specific symptoms. Therefore, novel therapies need to be developed to alleviate disease phenotypes by restoring normal MECP2 expression. An autologous hematopoietic stem cell and gene therapy approach for Rett syndrome may offer a benefit to affected patients by systemic delivery of functional MeCP2, including to affected neurons in the central nervous system.MethodsIn our current experiments, we evaluated the therapeutic effect of MECP2 lentiviral vector transduced human CD34+ hematopoietic stem and progenitor cells after transplantation into an immunodeficient mouse model of Rett syndrome.ResultsWe observed improvement of Rett syndrome-related phenotypes including the reversion toward normal motor abilities in an open field assay for total activity, horizontal activity, and vertical rearing activity, and an increased latency to fall in a rotarod assay. An increased level of MeCP2 protein was also observed in the brain tissue of transplanted mice.DiscussionBy providing functional MeCP2 to affected cells, our results highlight the ability of this strategy to improve Rett syndrome phenotypes. These proof-of-concept studies demonstrate the potential use of a stem cell gene therapy approach as a novel treatment for Rett syndrome patients.